The Effect Of Leadership Style, Work Facilities, Use Of Information Technology, And Benefits On Employee Work Motivation In Regional Development Planning Agency Nature Fence City - Aguslan, Fherla Yudhi; Hardiyansyah, Hardiyansyah; Aprini , NIsma (Journal of Indonesian Management, 2023)
This study aims to determine and analyze the influence of Leadership Style, Work Facilities, Use of Information Technology, and Allowances together on Employee Work Motivation at the Regional Development Planning Board of Pagar Alam City. This study uses quantitative research methods with respondents, namely employees of the Regional Development Planning Board of Pagar Alam City, totaling 41 respondents. Tests in this study used multiple linear regression analysis with the tools of the SPSS (Special Package and Service Solution) version 26 program.The results of the study show that Leadership Style, Work Facilities, Use of Information Technology, and Allowances have proven to have a significant effect on Employee Work Motivation at the Regional Development Planning Agency of Pagar Alam City, both partially and simultaneously.